School achievement as a predictor of depression and self-harm in adolescence: linked education and health record study. (6th March 2018) - Rahman, Muhammad A; Todd, Charlotte; John, Ann; Tan, Jacinta; Kerr, Michael; Potter, Robert; Kennedy, Jonathan; Rice, Frances; Brophy, Sinead
Abstract : Background: Mental disorders in children and adolescents have an impact on educational attainment. Aims: To examine the temporal association between attainment in education and subsequent diagnosis of depression or self-harm in the teenage years. Method: General practitioner, hospital and education records of young people in Wales between 1999 and 2014 were linked and analysed using Cox regression. Results: Linked records were available for 652 903 young people and of these 33 498 (5.1%) developed depression and 15 946 (2.4%) self-harmed after the age of 12 but before the age of 20. Young people who developed depression over the study period were more likely to have achieved key stage 1 (age 7 years) but not key stage 2 (age 11) (hazard ratio (HR) = 0.79, 95% CI 0.74–0.84) milestones, indicating that they were declining in academic attainment during primary school. Conversely, those who self-harmed were achieving as well as those who did not self-harm in primary school, but showed a severe decline in their attainment during secondary school (HR = 0.72, 95% CI 0.68–0.78). Conclusions: Long-term declining educational attainment in primary and secondary school was associated with development of depression in the teenage years. Self-harm was associated with declining educational attainment during secondary school only. Incorporating information on academic decline with other known risk factors for depression/self-harm (for example stressful life events, parental mental health problems) may improve risk profiling methods. Declaration of interest: None.